2010
DOI: 10.1099/jmm.0.019984-0
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of Pseudomonas aeruginosa in a mucin-containing synthetic growth medium mimicking cystic fibrosis lung sputum

Abstract: Pseudomonas aeruginosa airway infection is the leading cause of morbidity and mortality in cystic fibrosis (CF) patients. Various in vitro models have been developed to study P. aeruginosa pathobiology in the CF lung. In this study we produced a modified artificial-sputum medium (ASMDM) more closely resembling CF sputum than previous models, and extended previous work by using strain PAO1 arrays to examine the global transcription profiles of P. aeruginosa strain UCBPP-PA14 under early exponential-phase and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
197
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(214 citation statements)
references
References 50 publications
12
197
1
Order By: Relevance
“…Transcription of the virulence-related chitinase ChiB of Listeria monocytogenes and a chitinase from Enterococcus faecalis (efChi18A) has been shown to be upregulated in vitro in body fluids, such as blood and urine (Toledo-Arana et al, 2009;Vebø et al, 2009;Vebø et al, 2010). Similarly, chitinase upregulation has also been seen during growth of P. aeruginosa in artificial cystic fibrosis sputum (Fung et al, 2010), which is in agreement with the fact that the expression of a P. aeruginosa chitinase is enhanced in clinical isolates as compared with that in a laboratory strain (Salunkhe et al, 2005).…”
Section: Expression and Secretion Of Chitinases And Cbps During Infecmentioning
confidence: 81%
“…Transcription of the virulence-related chitinase ChiB of Listeria monocytogenes and a chitinase from Enterococcus faecalis (efChi18A) has been shown to be upregulated in vitro in body fluids, such as blood and urine (Toledo-Arana et al, 2009;Vebø et al, 2009;Vebø et al, 2010). Similarly, chitinase upregulation has also been seen during growth of P. aeruginosa in artificial cystic fibrosis sputum (Fung et al, 2010), which is in agreement with the fact that the expression of a P. aeruginosa chitinase is enhanced in clinical isolates as compared with that in a laboratory strain (Salunkhe et al, 2005).…”
Section: Expression and Secretion Of Chitinases And Cbps During Infecmentioning
confidence: 81%
“…Artificial sputum medium (Fung et al, 2010) contained 20 mg ml À 1 pig stomach mucin (Sigma-Aldrich, St Louis, MO, USA), 1.4 mg ml À 1 DNA, (Salmon Sperm DNA, Sigma-Aldrich), 2.2 mg ml À 1 KCl, 5 mg ml À 1 NaCl, 7.225 Â amino acids (Sigma-Aldrich), 14.45 Â MEM-Non-Essential amino acids (SigmaAldrich) and 0.005% egg yolk emulsion (Dalynn Biologicals, Calgary, AB, Canada). The media was modified to include 3 mg ml À 1 ferritin as an alternate iron source to more appropriately reflect the conditions of the CF lung (Stites et al, 1998;Reid et al, 2004;Ghio et al, 2012;Hare et al, 2012).…”
Section: Inoculation Of Wincf Systemmentioning
confidence: 99%
“…Based on these studies one would expect there to be more overlap between the transcriptomes of the anr and rsmA mutants, which suggests that experimental conditions may be crucial when using transcriptome profiling to study RsmA regulation. However, the RsmA regulatory profiles do exhibit substantial overlap with the profiles from microaerobic growth conditions in biofilms and in artificial sputum media (Fung et al, 2010;Waite & Curtis, 2009), whereby the transcriptional regulator PtxS, and genes associated with phenazine, PQS production and early biofilm formation, are modified in common. It has been reported that a subtle environmental difference can exert significant variation in the control of target genes of the Gac/Rsm pathway (Ventre et al, 2006), and therefore a fine balance can exist between positive and negative regulation of target genes by RsmA.…”
Section: Discussionmentioning
confidence: 99%